2020
DOI: 10.1088/1757-899x/869/6/062041
|View full text |Cite
|
Sign up to set email alerts
|

The impact of proptech on real estate industry growth

Abstract: The real estate industry is currently undergoing a digital transformation that not only changes its nature in terms of the markets and work environments, but is also influencing its growth. What are the main trends and concerns related to this transformation? To what extent is the real estate industry already prepared for this? This paper reviews the situation in terms of the emergence of a phenomenon known as PropTech. PropTech is characterized by the massive implementation of emerging technology such as home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 10 publications
0
38
0
4
Order By: Relevance
“…For Saull et al (2020), it is a movement that promotes a change in mentality within the sector and its consumers. Siniak et al (2020) define proptech as the massive implementation of emergent technology in the real estate sector.…”
Section: Proptech: the Concept And Evolutionmentioning
confidence: 99%
See 3 more Smart Citations
“…For Saull et al (2020), it is a movement that promotes a change in mentality within the sector and its consumers. Siniak et al (2020) define proptech as the massive implementation of emergent technology in the real estate sector.…”
Section: Proptech: the Concept And Evolutionmentioning
confidence: 99%
“…Proptech 2.0 began in the 2000s, when technology emerged in the traditional real estate sector, creating process efficiencies through automation, scale and uniformity (Baum, 2017;Baum et al 2020). Data analysis and the beginning of virtual reality offered better and more specialized services (Siniak et al, 2020), in addition to optimizing consumer experiences, inspiring new agents and other more consolidated ones to invest in their development (Blair Equity Research, 2015).…”
Section: Proptech: the Concept And Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Available studies have shown that efforts were concentrated on many aspects of this issue. These included the relevance and application of ICT in estate surveying and valuation (Chiedu, 2010;Ibisola et al, 2015); factors influencing the use of ICT (Adeyemo et al, 2015;); impact of information technology on real estate income (Jud et al, 2002); application of GIS in estate management (Olaniyi et al, 2006); technology /digital disruption in real estate industry (Deloitte, 2015;Lizam, 2019;Reding et al, 2014) and PropTech evolution (Aihie, 2019;Baum, 2017;Baum et al, 2020;Olufunso, 2019;Siniak et al, 2020;Tagliaro et al, 2021). However, studies on awareness and usage of mobile technology have been limited.…”
Section: Review Of Past Studiesmentioning
confidence: 99%